ENaC, iNOS, mucins expression and wound healing in cystic fibrosis airway epithelial and submucosal cells. (21st January 2014) - Hussain, Rashida; Umer, Hafiz Muhammad; Björkqvist, Maria; Roomans, Godfried M.
Abstract We compared airway epithelial cell models relevant for cystic fibrosis (CF): 16HBE cells with endogenous wild‐type cystic fibrosis transmembrane conductance regulator (CFTR), CFBE cells with mutated ΔF508‐CFTR, corrected CFBE cells overexpressing CFTR, CFSME (CF submucosal) and Calu‐3 (non‐CF submucosal) cells with respect to the epithelial sodium channel (ENaC), inducible NO synthase (iNOS) and mucins (MUC) (studied by quantitative Real‐Time‐Polymerase Chain Reaction, qRT‐PCR and Western blot), and wound healing. CFBE cells had significantly more expression of β‐ and γ‐ENaC mRNA and of β‐ENaC protein than 16HBE cells. Compared to corrected CFBE cells, CFBE cells had increased mRNA expression of all ENaC subunits and β‐ENaC protein. For ENaC, the CFSME/Calu‐3 mRNA ratio was very low and contradictory to the ENaC upregulation in CF cells. CFBE cells showed decreased expression of iNOS at both mRNA and protein levels compared to 16HBE cells and only at the mRNA level compared to corrected CFBE cells. CFSME cells showed expression of iNOS whereas Calu‐3 cells did not. Higher expression of MUC2 and MUC5B was found in corrected CFBE cells compared to CFBE cells. Wound healing in CFBE cells was delayed compared to corrected CFBE cells, but not to 16HBE cells, and in CFSME cells compared to Calu‐3 cells. Our data suggest CFSME as an inappropriate CF cell model for Calu‐3 cells, and provide partial support for the theory that the differences (in ENaC, iNOS and wound healing) between these cell lines are associated to the presence of CFTR in the bronchial airway epithelial cells.